New synthetic chitosan derivatives bearing benzenoid/heterocyclic moieties with enhanced antioxidant and antifungal activities. (1st December 2020) - Mi, Yingqi; Zhang, Jingjing; Chen, Yuan; Sun, Xueqi; Tan, Wenqiang; Li, Qing; Guo, Zhanyong
Highlights: Chitosan derivatives bearing benzenoid / heterocyclic moieties were synthesized. The structure was confirmed by means of FTIR, 1 H NMR, and elemental analysis. Chitosan derivatives showed significant improvement in antioxidant activity. The introduction of halogenated benzene is more effective on antifungal activities. Abstract: In this paper, several novel chitosan derivatives bearing benzenoid / heterocyclic moieties were synthesized via introducing aminobenzene and heterocyclic compounds onto carboxymethyl chitosan. The specific structures of chitosan derivatives were confirmed by FTIR, 1 H NMR, and elemental analysis. Meanwhile, the antioxidant efficiencies of chitosan derivatives were assayed in vitro . In particular, all chitosan derivatives showed significant improvement in superoxide-radical scavenging activity and DPPH radical scavenging activity. Their antifungal activities against two plant pathogenic fungi ( Colletotrichum lagenarium and Phomopsis asparagi ) were estimated in vitro by hyphal measurement, and all products exhibited excellent antifungal activity. Besides, the cytotoxicity of them was also measured by CCK-8 in vitro on L929 cells, and all samples showed low cytotoxicity. The good biocompatibility and enhanced biological activity of new synthetic chitosan derivatives might be obvious advantages, while applied in wide range of applications as antifungal agents or antioxidants in food, medicine, cosmetics, and other fields.